RATIO ANALYSIS TO ASSESS FINANCIAL PERFORMANCE IN THE PURWOREJO DISTRICT BUDGET REALIZATION REPORT FOR 2017-2020 - Lilis Lestyaningrum; Nibras Anny Khabibah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to determine the financial performance of Purworejo district in 2017-2020 by using the ratio of the degree of fiscal decentralization, the ratio of regional financial independence, the ratio of regional dependence, the ratio of effectiveness, and the ratio of efficiency. This is a qualitative research using secondary data taken from the official website of Purworejo district, namely https://purworejokab.go.id. The findings highlight that the financial performance of Purworejo Regency is still lacking when seen from the ratio of the degree of fiscal decentralization, the ratio of regional financial independence is still very low, the Regional Dependency Ratio is still very high. However, the Effectiveness Ratio has been very effective, and the Efficiency Ratio has also been efficient.